¿Los últimos pacaguaras? - Diego Villar (Caravelle)
Late Colonial documents about Bolivian Amazonia show us the ubiquity of «Pacaguara» Indians. However, during the second half of the 20th Century, several discourses by missionaries, scientists, politicians and even journalists regret the imminent extinction of the «the last of the Pacaguaras», hardly a dozen individuals settled with the Chacobo of Alto Ivon since the 1960s. Contrary to this fatalism, the National Census of 2012 reveals a surprising number of 161 Pacaguara. The paradoxical reasons of this demographic boom are discussed in terms of the indigenous and external manipulation of the representations of ethnic identity.